THE DIFFERENCE BETWEEN ZIRCONIUM CROWNS AND STAINLESS STEEL CROWNS IN THE PROSTHETICS OF PREMOLARS (American Journal of Pedagogical and Educational Research, 2023)
One of the reasons for the refusal to use CAD/CAM technologies in dentistry are reports of the insolvency of all-ceramic frame restorations made of polycrystalline ceramics based on zirconium dioxide and the chipping of veneers [1, 2]. The discrepancy in the recommendations for the manufacture of frame all-ceramic restorations raises a number of questions. Sandblasting is still widely used to improve surface roughness, strengthen the bond between the veneer and the frame and increase the strength of the joint during cementing.